Application of Game Based Learning Using Crossword Media in Improving English Vocabulary - Ni Tagel Rahini; I Nyoman Sudirman; I Wayan Numertayasa (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
English has become an important international language in communication between countries, business, technology, and access to educational resources around the world. In this case, English language skills are not only a necessity, but also a competitive advantage in facing global competition. However, unfortunately, English learning for Selat village students is currently still not achieving maximum results due to the low interest in learning and motivation of students in learning English vocabulary. Therefore, this research was conducted with the aim of increasing children's understanding of basic English vocabulary in Selat Village through the application of Game Based Learning (GBL) with Crossword media. The method used is PALS (Participatory Action and Learning System), namely a participatory approach that involves students and teachers in planning, implementing and evaluating learning actions. Initial problem identification indicates low mastery of English vocabulary and lack of student motivation. The improvement plan is in the form of implementing Game Based Learning using crossword puzzles. The results showed a substantial increase in students' understanding and memorization of English vocabulary, with students' positive response and enthusiasm for this learning method. The conclusion of this research is that Game Based Learning using crossword puzzles is effective in increasing students' understanding of basic English vocabulary in Selat Village.